Sigma 1 Receptor Co-Localizes with NRF2 in Retinal Photoreceptor Cells - Shannon R. Barwick; Mevish S. Siddiq; Jing Wang; Haiyan Xiao; Brendan Marshall; Elizabeth Perry; Sylvia B. Smith (Antioxidants, 2021)
Sigma 1 receptor (Sig1R), a modulator of cell survival, has emerged as a novel target for retinal degenerative disease. Studies have shown that activation of Sig1R, using the high affinity ligand (+)-pentazocine ((+)-PTZ), improves cone function in a severe retinopathy model. The rescue is accompanied by normalization of levels of NRF2, a key transcription factor that regulates the antioxidant response. The interaction of Sig1R with a number of proteins has been investigated; whether it interacts with NRF2, however, is not known. We used co-immunoprecipitation (co-IP), proximity ligation assay (PLA), and electron microscopy (EM) immunodetection methods to investigate this question in the 661W cone photoreceptor cell line. For co-IP experiments, immune complexes were precipitated by protein A/G agarose beads and immunodetected using anti-NRF2 antibody. For PLA, cells were incubated with anti-Sig1R polyclonal and anti-NRF2 monoclonal antibodies, then subsequently with (−)-mouse and (+)-rabbit PLA probes. For EM analysis, immuno-EM gold labeling was performed using nanogold-enhanced labeling with anti-NRF2 and anti-Sig1R antibodies, and data were confirmed using colloidal gold labeling. The co-IP experiment suggested that NRF2 was bound in a complex with Sig1R. The PLA assays detected abundant orange fluorescence in cones, indicating that Sig1R and NRF2 were within 40 nm of each other. EM immunodetection confirmed co-localization of Sig1R with NRF2 in cells and in mouse retinal tissue. This study is the first to report co-localization of Sig1R-NRF2 and supports earlier studies implicating modulation of NRF2 as a mechanism by which Sig1R mediates retinal neuroprotection.